Virtual Modeling of an Industrial Robotic Arm for Energy Consumption Estimation - Jin-Siang Shaw; Yi-Hua Huang (Advances in Technology Innovation, 2023)
This study aims to improve the traditional control methods of industrial robotic arms for path planning in line with efforts to conserve energy and reduce carbon emissions. The digital twin of a six-axis industrial robotic arm with an energy consumption model is innovatively designed. By directly dragging the end effector of a digital twin model, the robotic arm can be controlled for path planning, allowing path tuning to be easily made. In addition, the dynamic equation of the industrial robotic arm is derived, and the energy consumption of the corresponding path can be estimated. Four cases are designed to test the validity of the digital twin. Experimental results show that the physical robotic arm follows its digital twin model with the corresponding energy consumption computed. The estimated energy consumptions agree quite well with each designed case scenario.